Health Information Management by Record Officers: A Study of Military Hospitals in Lagos Metropolis - Ladan, Abubakar; Daura, Umma Dauda (MiddleBelt Journal of Library and Information Science, 2015)
The study seeks to generate information on the patients’ records management by Record Officers in military hospitals in Nigeria. The objective of the study was to identify the types of patients’ records created and maintained by military hospitals, the procedure adopted for the management of the records, retention and disposal of unwanted records and challenges associated with the patients’ records management in the military hospitals of 68 Nigerian Army Reference Hospital Yaba; Nigerian Navy Reference Hospital Ojo; Military Hospital Ikoyi and 445 Nigerian Air force Hospital Ikeja. Qualitative research methodology was used for the study; data was collected through interview. The findings of the study revealed the types of patients’ records created and procedure adopted for the management of the records which include case files/folders, report book and X-ray film. The findings also revealed that lack of ICT facilities, absent of finding aids, inadequate space and storage facilities as the challenges associated with the management of patients’ records in the hospitals studied. Recommendations were provided in order to overcome such challenges which include Provision of ERM software to replace traditional method of managing records, provision of storage facilities and space.